Aging Gut-Brain Interactions: Pro-Inflammatory Gut Bacteria Are Elevated in Fecal Samples from Individuals Living with Alzheimer’s Dementia - Alison I. C. Donaldson; Claire L. Fyfe; Jennifer C. Martin; Ellen E. Smith; Graham W. Horgan; Phyo K. Myint; Alexandra M. Johnstone; Karen P. Scott (Geriatrics)
Background/Objectives: Alzheimer’s disease (AD) is the most common form of dementia, characterized by an irreversible decline in cognitive function. The pathogenesis of several neurodegenerative disorders has been linked to changes in the gut microbiota, transmitted through the gut-brain axis. Methods: We set out to establish by case-control study methodology whether there were any differences in the composition and/or function of the gut microbiota between older resident adults in care homes with or without an AD diagnosis via analysis of the microbial composition from fecal samples. Results: The microbial composition, determined by 16S rRNA gene profiling, indicated that AD sufferers had significantly increased proportions of Escherichia/Shigella and Clostridium_sensu_stricto_1, and significantly decreased proportions of Bacteroides, Faecalibacterium, Blautia, and Roseburia species. The increase in potentially pro-inflammatory bacteria was consistent with slightly higher concentrations of calprotectin, a biomarker of gut inflammation. Fecal concentrations of most microbial metabolites measured were similar across groups, although participants with AD had significantly increased proportions of the branched-chain fatty acid, iso-butyrate, and lower overall concentrations of total short chain fatty acids. Conclusions: Participants with Alzheimer’s disease have several key differences within their gut microbiota profile, in contrast to care home residents without Alzheimer’s disease. The altered microbiome included both compositional and functional changes linked to poorer health and gut inflammation.